EDUKASI PELESTARIAN WARISAN BUDAYA TAK BENDA PADA MASYARAKAT NAGARI SIJUNJUNG, SUMATERA BARAT - Eka Meigalia; Yerri Satria Putra; Bahren Bahren (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Nagari Sijunjung has become a concern of various parties since registering Jorong Padang Ranah and Tanah Bato as world heritage and traditional villages. Both regions have many big houses, which is one of the essential bases for registration. However, apart from the big houses and their physical architecture, Nagari Sijunjung, especially Padang Ranah and Tanah Bato, have much intangible cultural heritage stored in the memory of a small part of the community. This intangible cultural heritage is neglected and forgotten, even though it can be an essential part of the registration to UNESCO. This activity aims to provide knowledge and understanding to the people of Padang Ranah and Tanah Bato about the importance of their intangible cultural heritage and document the intangible cultural heritage that exists in Padang Ranah and Tanah Bato, Nagari Sijunjung. This activity was carried out in Padang Ranah and Tanah Bato Nagari Sijunjung, West Sumatra. The methods used in this counseling are lectures and discussions. Documentation of this activity is also carried out by producing intangible cultural archives. The results of the activities obtained are counseling and documentation activities carried out by the people of Padang Ranah and Tanah Bato. They can understand and begin to document the intangible cultural products they have. They also do not hesitate to pass it on to the younger generation, so they do not just disappear. Archiving efforts are also needed as supporting documents for the existence of cultural heritage owned by the community. Through this activity, the people of Padang Ranah and Tanah Bato are expected to understand and also begin to become products of their intangible culture.